Toll-like receptor 3 acts as a suppressor gene in breast cancer initiation and progression: a two-stage association study and functional investigation. (3rd June 2019) - Fan, Lei; Zhou, Peng; Hong, Qi; Chen, Ao-Xiang; Liu, Guang-Yu; Yu, Ke-Da; Shao, Zhi-Ming
ABSTRACT: Toll-like receptor 3 (TLR3) is a receptor recognizing double-stranded RNA (dsRNA) from viruses as well as from lytic mammalian cells. In the present study, we performed a two-stage association study (n = 3, 551) and found that the minor alleles of two SNPs (the T-allele of rs5743312 and the T-allele of rs3775296) conferred increased risks of breast cancer incidence. The adjusted odds ratios (ORs) were 2.281 (P = 7.01 × 10 −5 ) and 2.086 (P = 8.69 × 10 −5 ), respectively. Specifically, the susceptibility variants within TLR3 were significantly associated with larger tumor size (adjusted P-values: 0.004 for rs5743312 and 0.004 for rs3775296). Furthermore, we investigated the biological function of the TLR3 protein in breast cancer cell lines. Notably, the stable expression of TLR3 directly inhibited cell proliferation both in vitro and in vivo . We also verified that TLR3 conferred less invasive phenotypes on breast cancer cells by regulating the mRNA expression of a panel of genes. TLR3-mediated inhibition of proliferation was caused by downregulation of the EGFR/PI3K/AKT pathway. In summary, our findings strongly suggest that common genetic changes in the TLR3 gene may influence breast cancer susceptibility and development, and TLR3 plays a negative regulatory role in the initiation and progression of human breast cancer cells, at least in part by downregulating the EGFR/PI3K/AKT pathway.